(untitled) (Revista Apotheke, 2025)
This article analyzes the transdisciplinarity of drawing because of its importance in various areas of knowledge.Through an in-depth analysis, it seeks to understand drawing as a mental tool and methodology of analysis and reflection, fostering perceptual, intellectual and cognitive development. This approach is reinforced by the ideas of architect Campo Baeza and plastic artist Joseph Beuys. The article establishes a dialogue between primitive and contemporary representations, highlighting the fusion between the natural and the artificial, accentuated by the industrial revolutions. Through the legacy of artists like William Turner, we witness the climatic changes of the First Industrial Revolution, resulting from technological development. Connections are made between drawing as a manual technology and its incorporation into technological devices, altering human and environmental relations. The thought of Walter Benjamin is used to reflect on current images and modes of production. Work methodologies with 3D drawing software are analyzed, detaching drawing from conventional supports and tools. Projects like LABVERDE and EcoArt Project are mentioned, as well as the work of Portuguese artists like Pedro Vaz, Cristina Ataíde and Vanessa Barragão.